Experimental drought forecast for Limpopo River Basin - Vigneswaran, Kayathri; Ghosh, Surajit; Dickens, Chris; Garcia Andarcia, Mariangel (International Water Management Institute, 2024)
This brief focuses on drought forecasting in the Limpopo River Basin (LRB), a transboundary river basin in southern Africa that spans South Africa, Botswana, Zimbabwe, and Mozambique. The study addresses the significant impacts of droughts on agriculture, water resources, and livelihoods in the region, exacerbated by climate variability and change. Utilizing the Standardized Precipitation Index (SPI), derived from both historical and forecasted precipitation data, the study evaluates drought conditions from 2023 to 2024, based on data from the Climate Hazards Group InfraRed Precipitation with Station (CHIRPS) dataset and European Centre for Medium-Range Weather Forecasts (ECMWF) seasonal forecasts.